Lack of TYK2 signaling enhances host resistance to Candida albicans skin infection - Sara Miranda; Caroline Lassnig; Kristina Schmidhofer; Hrönn Kjartansdottir; Claus Vogl; Simone Tangermann; Irina Tsymala; Verena Babl; Mathias Müller; Karl Kuchler; Birgit Strobl (Nature Communications)
Abstract Candida albicans is the most common human fungal pathogen, causing diseases ranging from local to life-threating systemic infections. Tyrosine kinase 2 (TYK2), a crucial mediator in several cytokine signaling pathways, has been associated with protective functions in various microbial infections. However, its specific contribution in the immune response to fungal infections has remained elusive. In this study, we show that mice lacking TYK2 or its enzymatic activity exhibit enhanced resistance to C. albicans skin infections, limiting fungal spread and accelerating wound healing. Impaired TYK2-signaling prompted the formation of a distinctive layer of necrotic neutrophils around the fungal pathogens. Transcriptomic analysis revealed TYK2’s pivotal role in regulating interferon-inducible genes in neutrophils, thereby impacting their antifungal capacity during infection. Furthermore, we show that TYK2-dependent interferon-gamma (IFNγ) production contributes to fungal dissemination from the skin to the kidneys. Our study uncovers a hitherto unrecognized detrimental role of TYK2 in cutaneous C. albicans infections.